Phylogeny and classification of the bucconidae (Aves, galbuliformes) based on osteological characters - Posso, Sérgio Roberto; Donatelli, Reginaldo José [UNESP]; Piacentini, Vitor Q.; Guzzi, Anderson (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2020)
The puffbirds (Bucconidae) are relatively poorly studied birds whose intrafamilial relationships have not yet been explored within a phylogenetic framework in a published study. Here, we performed a parsimony analysis of osteological data obtained following the examination of all the genera and 32 out of the 36 species recognized in Bucconidae currently. The analysis yielded eight equally parsimonious trees (426 minimum steps). Ambiguous relationships were observed only in Notharcus ordii, Malacoptila fusca, and Nonnula rubecula. Notably, Bucco was polyphyletic, leading to the resurrection of Cyphos and Tamatia. In addition, the osteological data provided a well-resolved phylogeny (topological dichotomies) and the support indices indicated that most of the nodes were robust at all hierarchical levels. We thus propose the first revised classification of the Bucconidae.
Keywords: Morphology; Puffbirds; Systematics